Antecedents of graduate student satisfaction through e-portfolio: content analysis. Issue 9 (25th July 2019) - Shea, Timothy; Parayitam, Satyanarayana
Abstract : Purpose: Using content analysis on assessment of a student's learning, the purpose of this paper is to investigate the effect of teaching on students through self-disclosure in E-portfolios. The antecedents of graduate student satisfaction are studied using a conceptual model. Design/methodology/approach: The data from 50 E-portfolios from senior MBA students was analyzed following the steps outlined by Krippendorff (2004). A conceptual model was developed and tested using hierarchical regression. Teaching tools and delivery method by the professors were the moderators in the relationship between learning, professor dedication and teaching tools and student satisfaction. Findings: The results suggest learning, professor dedication, course content, faculty engagement and teaching method are positively related to student satisfaction. Results also suggest that teaching tools moderate the relationship between learning and student satisfaction, and delivery method moderates the relationship between faculty engagement, professor dedication and student satisfaction. Research limitations/implications: The present research is based on self-report documents from E-portfolios of MBA students from an accredited university in north-eastern part of Massachusetts. Since the authors used content analysis, the limitations of social desirability bias and common method bias are not limitations which are inherent in self-report structured instruments. The research has implications for the higher educational institutions and studies in the field of education. Practical implications: In addition to the students and faculty in educational institutions, the present study contributes to literature on E-portfolios and also for Association to Advance Collegiate Schools of Business accreditations. The implications for both academicians and practitioners are discussed. Social implications: The findings from the study help in creating a fruitful academic environment in organizations. Originality/value: The study provides new insights into the effect of learning, teaching method, delivery method, professor dedication on student satisfaction.